1999
DOI: 10.1084/jem.189.10.1621
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Nitric Oxide Synthases 1, 2, and 3 to Airway Hyperresponsiveness and Inflammation in a Murine Model of Asthma

Abstract: Asthma is a chronic disease characterized by increased airway responsiveness and airway inflammation. The functional role of nitric oxide (NO) and the various nitric oxide synthase (NOS) isoforms in human asthma is controversial. To investigate the role of NO in an established model of allergic asthma, mice with targeted deletions of the three known isoforms of NOS (NOS1, 2, and 3) were studied. Although the inducible (NOS2) isoform was significantly upregulated in the lungs of ovalbumin (OVA)-sensitized and -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
140
4
7

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 199 publications
(168 citation statements)
references
References 57 publications
(95 reference statements)
15
140
4
7
Order By: Relevance
“…In the same vein, it has been shown that acute inhibition of NOS2 activity either suppresses or exacerbates airway inflammation and chemokine expression (21,22). Our results and those of others (20) clearly indicate that airway inflammation is fully expressed in the absence of NOS2. Thus, the apparent conflict between studies that favor NO derived from NOS2 as a proinflammatory molecule with those that are opposed to this concept is likely due to differences in the immunization and challenge protocols, and to the concentration of NO produced.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…In the same vein, it has been shown that acute inhibition of NOS2 activity either suppresses or exacerbates airway inflammation and chemokine expression (21,22). Our results and those of others (20) clearly indicate that airway inflammation is fully expressed in the absence of NOS2. Thus, the apparent conflict between studies that favor NO derived from NOS2 as a proinflammatory molecule with those that are opposed to this concept is likely due to differences in the immunization and challenge protocols, and to the concentration of NO produced.…”
Section: Discussionsupporting
confidence: 74%
“…However, the role of NOS2 in allergic inflammation is controversial. For instance, Xiong et al (19) showed that NOS2 Ϫ/Ϫ animals presented an inhibited airway inflammation while De Sanctis et al (20) found no significant differences in airway inflammation or cellular recruitment into the airway space between NOS2 Ϫ/Ϫ and WT animals. In the same vein, it has been shown that acute inhibition of NOS2 activity either suppresses or exacerbates airway inflammation and chemokine expression (21,22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Strikingly, studies in mice with targeted deletions of the three isoforms of NOS also generated conflicting results. For instance, De Sanctis et al (1999) compared the asthmalike response of wild-type (WT) animals with those obtained in mice with NOS-deficiencies. The authors found that total NOS activity increased in sensitized and OVAchallenged WT animals as well as in NOS1 and 3 double KO animals, but not in NOS2-KO mice.…”
Section: Nos2 Inhibitors and Nos2-deficiency In Experimental Asthmamentioning
confidence: 99%
“…Controversial data was also generated in studies using NOS2 knockout mice. Xiong et al (1999), showed that NOS2 -/-animals presented a diminished airway inflammation while others clearly showed that airways inflammation is fully expressed in NOS2 -/-mice (De Sanctis et al 1999, Rodriguez et al 2003.…”
mentioning
confidence: 99%